2018
DOI: 10.1080/03008207.2018.1470167
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned media from human osteoarthritic synovium induces inflammation in a synoviocyte cell line

Abstract: Our study showed that K4IM might be a suitable in vitro model for evaluating different cellular pathways in OA studies. Importantly, we demonstrated that in OA, all joint tissues might be involved in the progression of synovitis with a predominant role of synovial membrane itself compared to the other joint tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 48 publications
0
55
0
Order By: Relevance
“…Favero et al observed the elevation of CCL21 and CCL5 in coculture of meniscus and synovial membrane from patients with osteoarthritis [47]. Conditioned media from osteoarthritis tissues like cartilage, IFP, meniscus, and synovium induced and enhanced production of CXCL8 and CCL21 in the synoviocyte cell line [67]. Several other studies showed an enhanced CCL2 level in patients with osteoarthritis [47,63,68].…”
Section: The Role Of Chemokines In Osteoarthritismentioning
confidence: 97%
“…Favero et al observed the elevation of CCL21 and CCL5 in coculture of meniscus and synovial membrane from patients with osteoarthritis [47]. Conditioned media from osteoarthritis tissues like cartilage, IFP, meniscus, and synovium induced and enhanced production of CXCL8 and CCL21 in the synoviocyte cell line [67]. Several other studies showed an enhanced CCL2 level in patients with osteoarthritis [47,63,68].…”
Section: The Role Of Chemokines In Osteoarthritismentioning
confidence: 97%
“…In addition to its involvement in early stages of the disease, synovial inflammation is also thought to be secondary to penetration of osteocartilaginous fragments and inflammatory/catabolic factors in the synovial cavity [21]. Interestingly, all OA joint tissues are able to stimulate synoviocytes and might be involved in the progression of OA synovitis [17].…”
Section: The Role Of the Ifp-synovial Membrane As A Functional Unimentioning
confidence: 99%
“…In this context, careful attention should be paid to a new emerging concept reconsidering the relation between the IFP and the synovial membrane, which are tissues innervated and well vascularized [15, 16]. Recently, it has also been shown that IFP in OA represents a source of inflammatory molecules and is more inflamed and vascularized compared to nonosteoarthritic controls (Figure 1) [1719]. Moreover, it has been known that IFP can be the cause of anterior knee pain [20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, attention has focused on the role of the IFP in OA pathophysiology [3,10,11]. It has been shown that IFP produces pro-inflammatory mediators inducing synovial inflammation and seems to act as an anatomo-functional unit with synovial membrane contributing to OA onset and progression [3,[10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%